Pendampingan Penyusunan Dokumen Rencana Pembangunan Jangka Menengah Desa - Indrastanti, Sri Retno; Bawono, Andy Dwi Bayu; Nursiam, Nursiam; Sari, Shinta Permata; Mukharomah, Wafiatun (Universitas Muhammadiyah Surakarta, 2010)
The aimed of this community service activity is to increase understanding ofthe village stakeholders, members of the BPD and community representatives in thevillage of Makamhaji, Sub District of Kartasura, District of Sukoharjo about theformulation of the Village Medium Development Planning (RPJMDesa) Document ,this activity also provides assistance preparation of Medium Development Plan-Village formulation so that it appears the draft Development Plan-Village Makamhaji accordance with the Regulation of the Minister of Home Affair (MoHA) number 37 and 66 in the Year 2007.The methods used in these activities include training activities, discussions anddocument preparation assistance, the Village Development Plan implemented whichdirectly implemented in the Village of Makamhaji. Training was conducted over 2days at the Village Makamhaji, which was attended by 23 participants and technicalassistance activity was conducted over 2 months after the training done to provideguidance and assistance in order to improve the preparation of the document draft ofthe Village Development Plan, this assistance activities take place in two places,firstly in department of Accounting FE UMS, and Village meeting room Makamhaji.As a result of training and technical assistance of planning preparation produced thedraft of medium development plan document in Villages Makamhaji 2006 - 2012which has been prepared jointly by the trainees with reference to source documentssuch as RPJMD Sukoharjo, Kartasura District Strategic Plan, Development PlanningConsultation document (Musrenbang ) Makamhaji Village, District KartasuraSukoharjo.